Information Theory in Molecular Evolution: From Models to Structures and Dynamics - Morcos, Faruck (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue collects novel contributions from scientists in the interdisciplinary field of biomolecular evolution. Works listed here use information theoretical concepts as a core but are tightly integrated with the study of molecular processes. Applications include the analysis of phylogenetic signals to elucidate biomolecular structure and function, the study and quantification of structural dynamics and allostery, as well as models of molecular interaction specificity inspired by evolutionary cues.